Dense calcium and lesion-specific ischemia: A comparison of CCTA with fractional flow reserve. (May 2017) - Baskaran, Lohendran; Ó Hartaigh, Bríain; Schulman-Marcus, Joshua; Gransar, Heidi; Lin, Fay; Min, James K.
Abstract: Background and aims: Studies evaluating the relationship between dense coronary calcium (DC) and myocardial ischemia have had incongruent results. We sought to clarify whether DC, as detected by computed coronary tomographic angiography (CCTA), is an independent predictor of ischemia as measured by invasive fractional flow reserve (FFR). Methods: In total, 249 (399 lesions) stable patients undergoing CCTA and invasive FFR were enrolled for this post-hoc analysis. DC was defined as plaque with ≥350 HU using quantification software, and ischemia was defined as FFR ≤0.80. We evaluated the relationship of dense calcium volume (DCV), lesion plaque volume (LPV), non-calcified plaque volume (NCV), and area stenosis (AS) with ischemia using logistic regression reporting odds ratios (OR) with 95% confidence intervals (95% CI). Results: Mean age was 63.0 ± 8.6 years, and 73 (29.3%) were female. Mean DCV was higher in lesions with FFR ≤0.80 (57.0 ± 54.7 mm 3 vs. 37.6 ± 49.5 mm 3, [ p  < 0.001]). DCV and LPV were closely correlated (Pearson's coefficient = 0.49 [ p  < 0.001]). After adjustment for AS, LPV (OR 1.01, 95% CI 1.00–1.04, p  < 0.001) but not DCV (OR 1.01, 95% CI 0.96–1.06, p  = 0.69) was independently associated with ischemia. Conclusions: Dense calcium is not an independent predictor of ischemia, but rather a marker of aggregate LPV, which in turn, is predictive of ischemia. Highlights: The association between dense coronary calcium and ischemia is unclear. We evaluated the relationship using coronary computed tomography angiography (CCTA) and fractional flow reserve (FFR). Dense coronary calcium is not an independent predictor of ischemia, but a surrogate. Lesion plaque volume is an independent predictor of ischemia.